Report from the 4th Strategic Workshop on Information Retrieval in Lorne (SWIRL 2025) - Trippas, Johanne R.; Culpepper, J. Shane; Aliannejadi, Mohammad; Allan, James; Amigó, Enrique; Arguello, Jaime; Azzopardi, Leif; Bailey, Peter; Callan, Jamie; Capra, Rob; Craswell, Nick; Croft, Bruce; et al. (SIGIR forum)
The purpose of the Strategic Workshop on Information Retrieval in Lorne (SWIRL)1 is to explore the long-range issues of the information retrieval (IR) field, to recognise challenges that are on – or even over – the horizon, to build consensus on key challenges, and to disseminate the resulting information to the research community. The intent is that this description of open problems will help to inspire researchers and graduate students to address the questions and will provide funding agencies with data to focus and coordinate support for IR research. Date: 10–12 February 2025. Website: https://sites.google.com/view/swirl2025/home.